ALGORITHM OF DETERMINATION OF OPTIMAL POWER PARAMETERS OF THERMAL FURNACE WITH BIOGAS HEATING AT PRESENCE OF SPATIAL ELECTRIC PAUL IN ITS CHAMBER - Kovalenko , Victor (Scientific Journal "Metallurgy", 2020)
Lately power resources, consumed by industrial plants, occupy all greater part in the structure of cost of price through their swift rise in prices, and in particular natural gas, as one of main types of fuel. Therefore the use of alternative and refurbishable energy sources, especially in industry, acquires all greater actuality. Introduction of biogas technologies, first of all, in metallurgical industry for energy-supply of thermal and heater furnaces as the least demanding from the technological point of view to aggressive chemical composition of biogas mixtures, can become by the increase of competitiveness of production through more subzero cost of biogas as a primary fuel for the mentioned equipment. On the first stage there are executed experimental researches on the concrete object of industrial enterprise for the sake of establishment of intercommunication between the parameters of the furnace setting, such as: expense of biogas mixture (Q); by voltage between a purveyance and gas-ring (U); by the sizes of purveyance (x, y, z), On results the executed planning of experiment in accordance with the matrix made for this purpose a necessary mathematical model get. On the second stage there are carried out bringing of necessary weekend of data such as: chart of heating of furnace, current temperature and temperature, which is set by technology. For simplification of calculations on the base of the worked out algorithm in the environment of "Excel" a programmatic complex by means of which possibly with the minimum expense of time to define all possible combinations of values of expense of gas mixture and size of voltage in a certain range with the fixed step and to set most economic advantageous from them is realized, for which arrive at the temperature set by a chart in every his point. The algorithm of determination of optimal power parameters of thermal furnace, working on biogas mixture, at presence of electric-field in its chamber is offered. Executed Calculation of economy efficiency of the offered method on the example of equipment of rental workshop of metallurgical plant is carried out.